PERRAULT'S SYNDROME: A CLINICAL AND GENETIC INVESTIGATION OF THREE SISTERS - P. Mehdipour; A.R. Karimi; MM. Bastanhagh (Acta Medica Iranica, 1999)
Perrault's syndrome (P.S.) is rare. The combination of gonadal dysgenesis and hearing loss was accompanied by 46,XXkaryotype in three sisters with parental consanguineous marriage. Genetic investigation revealed normal female karyotype, positive liarr and negative fluorescence iPj-bodies, which was confirmed by molecular study on the basis of fluorescence in situ hybridization (PISH), with application of Keen probe, showing the presence of two signals in 95% of the cells of these 3 Iranian sisters. The pedigree showed parental consanguinity (first cousin) with an autosomal mode of inheritance for both Perrault's syndrome and hearing loss. These findings together with normal thyroid function, serum prolactin, high level of .serum gonadotropins is similar to the menopausal period in all 3 sisters. Estrogen and progesterone were recommended for all 3 sisters. This combined therapy led to mensturation and after a few montfis their breasts were normally developed. Tor further management cochlear implantation, speech therapy and training courses were suggested in order to improve hearing and intellectual abilities.